People and Social Progress - Smirnovas, Anatolijus (Problemos, 1970)
On the basis of Marxist-Leninist methodology an attempt is made in the paper to give the definition of people as a sociological category in view of the role it plays as the subject of social progress. In the socialist society people differ qualitatively from their counterpart in antagonistic social-economic formations. The socialist people present a new historic form of people, the one which came into existence as a natural result of the building of socialism. In the Soviet Union the socialist people exist in the form of the Soviet people who possess features and peculiarities common to the socialist people and bound up with the specific character of building socialism in the USSR.